International Spillovers of U.S. Monetary Policy - Ishak Demir (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2019)
We estimate a structural dynamic factor model on large panel quarterly data to analyse the spillovers of U.S. monetary policy to the advanced economies and emerging and frontier market economies. The estimated model suggests that monetary contraction in U.S. leads to a significant decrease in real GDP with typical inverted hump-shape almost for all countries. It reduces permanently aggregate price level, increases interest rate and leads appreciation of U.S. dollar. However, contagion of U.S. monetary policy to the individual countries shows heterogeneity. For instance, its impact is larger in developing countries. We also find that global financial crisis has amplified the impact of U.S monetary policy on the rest of world in particular on developing countries. Lastly, the empirical results suggest that the cross-country heterogeneity in responses may be consequence of difference in country-specific characteristics such as exchange rate regimes, currency of price settings of firms, central bank independence and geographical distance from Unites States.
Keywords: C38; E43; E52; E58; F42; G12; 330; cross-country heterogeneity; country-specific characteristic; international monetary spillovers; structural factor model; monetary policy